Characterization and Preclinical Perspectives of Organic Small Molecule Drug Metabolites in Drug-drug Interactions - Gao, Liqian; Chen, Jun; Hu, Yi; Sun, Hongyan; Siang Ong, Yong; Zhang, Jingxin; Chai, Zhifang; Seong Lee, Su (Current Organic Chemistry, 2016)
The potential of metabolites to contribute to drug-drug interactions (DDIs) has not been well defined so far. However, metabolites of parent drug compounds can contribute to both side effects and DDIs. To address this unmet challenge, we introduce recent advances as well as our perspectives of the metabolites in DDIs in this review. Firstly, we review several typical examples of organic small molecule drug metabolites as major contributors to DDIs in clinic. Since some of the metabolites are so important in the contributions to DDIs, we then further review how to identify active metabolites in vivo and when such metabolites should trigger DDI assessment. Lastly, we review in vivo animal models, especially humanized/chimeric mice, in improving the quality of preclinical DDI assessments.
Keywords: pharmacodynamics